Drug Shortages From the Perspectives of Authorities and Pharmacy Practice in the Netherlands: An Observational Study - Postma, Doerine J.; De Smet, Peter A. G. M.; Gispen-de Wied, Christine C.; Leufkens, Hubert G. M.; Mantel-Teeuwisse, Aukje K. (Frontiers in Pharmacology, 2018)
Background: Drug shortages are a potential threat to public health. Reliable data on drug shortages is limited. The objective was to examine the extent and nature of potential drug shortages signaled by authorities and pharmacy practice in the Netherlands Materials and methods: The primary working systems of Dutch authorities (Medicines Evaluation Board and Health and Youth Care Inspectorate) and the archives of pharmacy practice (Royal Dutch Pharmacists Association) from 2012 to 2015 were searched for number, characteristics, overlap, and date of signals on potential drug shortages. Also, the product characteristics of the potential drug shortages were analyzed from the two different sources Results: Authorities detected 2.6 times more signals on potential shortages than pharmacy practice. Only 438 (8%) out of 5,731 potential drug shortages were detected by both authorities and pharmacy practice. Signals were detected later by authorities than by pharmacy practice, especially on potential permanent shortages (median difference -180 days (IQR: -4 to -405 days)). Authorities detected by majority (72%) signals related to permanent shortages with relative overrepresentation of rectal products and anti-infectives for systemic use. In contrast, pharmacy practice detected by majority (71%) signals related to temporary shortages with relative overrepresentation of ocular and cutaneous products, anti-infectives for systemic use, products for sensory organs and dermatologicals. Conclusions: Authorities and pharmacy practice detected different signals for potential drug shortages with little overlap. Combining data from both authorities and pharmacy practice seems to be necessary in order to gain a more complete overview and maximum insight in potential drug shortages at a national level. Moreover, the finding that authorities were informed later than pharmacy practice causes concerns in terms of opportunities for authorities to assist pharmacy practice to find solutions for shortages.